Structural coupling in entrepreneurial families: how business-related resources contribute to enterpriseness. Issue 5 (27th May 2021) - Estrada-Robles, Mariana; Williams, Nick; Vorley, Tim
ABSTRACT: This paper examines how family members support each other's entrepreneurial activities through sharing resources created at the business-level. Drawing on the concept of 'enterpriseness' the study examines the flows between a family and the business and how it influences the impacts of the businesses on the family (enterpriseness). We capture the enterpriseness by focusing on entrepreneurial families where more than one member is an owner-entrepreneur. Through in-depth interviews with entrepreneurial families in Mexico, we show how different forms of capital resources emerging from multiple businesses flow back into the family and contribute to enterpriseness. The entrepreneurial family enables access to human, social and financial capital resources that are easily mobilized and combined by other members for their multiple firms, showing a subsequent effect to the business-level. Consequently, enterpriseness influences entrepreneurial behaviours which have a variety of consequences for the entrepreneurial family and their businesses. The paper concludes with a number of contributions to theory.